Effect of Kandangan Pump House on Long Storage Diversi Gunungsari in Sememi - Retsadika Kusriardi; Adi Prawito; Farida Hardaningrum (NAROTAMA UNIVERSITY, Indonesia, 2021)
The Surabaya City Government has built a box culvert in the Gunungsari Diversi channel for the Sememi segment to Banjar Sugihan and the Kandangan pump house. The purpose of this study is to describe and analyze the operational impact of the Kandangan pump on the Sememi box culvert capacity. Therefore, the Surabaya City Government built the Sememi box culvert as a long storage in the primary channel of the Gunungsari diversion in order to reduce inundation as well as function as a road that can overcome congestion in the area. The Surabaya City Government has also built a Kandangan pump house as an outlet rather than a long storage at the Gunungsari version. The reduction of inundation and congestion can increase the wheels of the economy which have a global impact on cities around Surabaya as well as a smoother access road for the people in West Surabaya to the middle of the city.